Konventionaliserede forbindelser med danske retningsadverbier Leksikografisk repræsentation og funktion - Hovmark, Henrik (Nordiske Studier i Leksikografi, 2007)
Conventionalized expressions: lexicographic representation and function. The semantics of Danish directional adverbs (DDA) (for instance op ’up’, ned ’down’, ud ’out’, ind ’in’) are closely connected to the semantics of other words, primarily verbs and prepositions (VB + DDA + PP). In this article, I explore the specific representation of conventionalized expressions with DDA, i.e. expressions which encode specific conceptualizations and semantic patterns, but which are not idiomatic or fixed. The representational solutions in two major monolingual Danish dictionaries, The Danish Dictionary and The Dictionary of the Insular Dialects, are described. Special attention is given to the possible lexicographic use potential of conventionalized expressions as linguistic items highly suitable for conveying information about semantic fields and typical use situations.